Isolation of Gram-negative bacteria from manguezal sediment samples is São Luís, Maranhão (Research, Society and Development, 2022)
Mangrove sediments are very moist and rich in decomposition organic matter, formed by a series of species resistant to tidal flow. This coastal ecosystem is formed by a series of species resistant to tidal flow, with soil containing a rich environment that limits the diversity of biomes. The objective of this study was the identification of microorganisms and the physicochemical characterization in sediment samples from two points of a mangrove located near a hospital on the island of São Luís, Maranhão. Two sediment samples were collected in appropriate tubes, stored and sent to the Environmental Microbiology Laboratory at CEUMA University. In the laboratory, aliquots were removed for the physical-chemical characteristics using a methodology as recommended by the Brazilian Agricultural Research Company (EMBRAPA), tracking characteristics such as granulometry, organic matter, organic carbon, nitrate and nitrite, total phosphorous and pH. The soil was characterized as organic, rich in nitrate, nitrite and mineral salts, with pH (6.3), characteristic of the mangrove ecosystem. Isolation, identification of MALDI-TOF isolates (Matrix-assisted Laser Desorption/Ionization Time-Of-Flight Mass Spectrometry) and antimicrobial susceptibility test used Kirby-Bauer methodology were performed. Gram-negative bacteria were identified, of the genus Ochrobactrum and thermotolerant species, such as Escherichia coli, which are considered pathogens that are indicators of lack of basic sanitation and that presented multiresistance in vitro to the antibiotics tested. Our study strengthens the idea of further research to evaluate the diversity of microorganisms present in mangroves to encourage and warn about the preservation and sanitary control of mangrove ecosystems.